Biostratigraphy, paleobathymetry and paleobiogeography of Lower Cretaceous benthic foraminifera from Shatsky Rise (ODP Leg 198) in the central Pacific Ocean - Giraldo-Gomez, VM; Petrizzo, MR; Erba, E; Bottini, C (Cretaceous Research, 2022)
Benthic foraminiferal assemblages at Ocean Drilling Program (ODP) holes 1207B, 1214A, 1213A, and 1213B drilled on Shatsky Rise (Pacific Ocean) provided an opportunity to compare all taxa recorded from the Hauterivian to the Albian. The benthic foraminiferal assemblage abundances and compositions confirm a progressive deepening of the Shirshov and Tamu Massifs during the Early Cretaceous. In the Hauterivian, recovered only at ODP holes 1213A and 1213B, an outer neritic setting (100-200 m) is inferred. Benthic foraminiferal assemblages display a deepening from an upper bathyal setting (200-500 m) through the Barremian to a lower bathyal (1000-2000 m) environment during the Albian. The comparison of the Pacific benthic foraminiferal assemblages with records worldwide indicates that, during the Hauterivian, only very few taxa documented at ODP holes 1213A and 1213B occurred in all bioprovinces (e.g., the Atlantic Ocean, the Western Tethys, the Indian Ocean, the Boreal, and the Antarctica), probably due to the shallow-water environment (outer neritic: 100-200 m) characterizing the Shatsky Rise. In contrast, benthic foraminiferal assemblages reveal degrees of affinities with species recorded especially in the Atlantic Ocean, the Boreal Province, and the Western Tethys throughout the Barremian-Albian interval. The cosmopolitan character of some benthic foraminifera probably suggests an interconnectivity of ocean basins in the Early Cretaceous. Concurrently, several benthic foraminiferal species were able to colonize many bioprovinces, demonstrating no predilection for any specific location or paleo-latitude. Site-specific paleobathymetry appears to be less relevant than geographic distances (biogeography) in explaining variations in benthic foraminiferal assemblages from Shatsky Rise and other bioprovinces.